Geoelectric Interpretation of Wenner-Schlumberger Configuration Using Res2Dinv Software: A Case Study of 2D Mapping of Seawater Intrusion in a Landslide Potential Area, North Halmahera District, Indonesia - Andrisal Tambanaung; Bayu Achil Sadjab; Kurnia Kurnia; Harsen Berg Janis; Masitah Yusniar; Oktosea Buka; Steven Iwamoni; Adrian Rahmat Nur (CV FOUNDAE, 2024)
Research has been carried out on landslides in Saluta-Pelita Village, North Galela District, North Halmahera Regency, Indonesia using the Wenner-Schlumberger method using a Geoelectric Resistivity tool - Naunira NRD 300 HF. This research aims to determine the structure of the subsurface layer in the potential landslide area of Saluta-Pelita Village. In addition, this research aims to determine the slip plane (boundary layer) of sea water intrusion in the research area. The measurement results are processed using Res2Dinv software for 2D resistivity which describes the subsurface layer shown in color. The measurement results on track 1 show a clay layer with a resistivity value of 3.1 ohm -27 ohm at a distance of 1-80 meters (blue and green), a silt layer of 44.3 ohm - 184.1 ohm at a depth of 1-20 meters (Yellow) which is a slip plane (boundary layer) of sea water intrusion with a path length of 40 meters, conglomerate 210 ohm (red) at a depth of more than 7.50 meters. In track 2 there is a layer of clay with a resistivity of 1.4 ohm - 39 ohm at a depth of 1-24 meters (blue and green), silt 43.1 m-185.6 m (yellow) is the slip plane (layer boundary) of sea water intrusion with a 95 meter long track, a conglomerate layer with a resistivity of 203.4 ohm - 407.8 ohm (red) at a depth of more than 12.8 meters. On track 3 there is a layer of clay with a resistivity of 0.186 ohm - 31.4 ohm (blue and green) at a depth of up to 24 meters with a length of more than 120 meters, silt with a resistivity value of 44.4 ohm - 189 ohm (yellow) which is a slip plane (boundary layer) sea water intrusion with a path of 65 meters at a depth of 2.50 meters-24.9 meters.